(untitled) (Experimental biology, 2023)
One of the promising ways to solve the problem of reducing areas, reducing the productivity of plantations, and the profitability of pear cultivation is the widespread involvement in the breeding process of new donors of valuable economic and biological traits and adaptive properties that the wild endemic species of Regel’s pear (Pyrus regelii Rehder), which grows in Turkestan region and endangered and subspecies of the common (forest) pear (Pyrus pyraster L.), growing in the south and southeast of Kazakhstan. The aim of the research was to identify the distribution areas of wild pear populations and save them in the Genebank. For the reliable conservation of species, modern areas of growth of pear populations have been clarified, identified, mapped, and an effective method of preserving seeds has been applied - cryopreservation in liquid nitrogen at ultra-low temperature. As a result of monitoring, 6 populations were identified, and the coordinates of tree growth were recorded in 16 areas of the Regel pear and 2 populations of the common pear. To create a Cryobank - in places of natural growth, fruits were collected during the period of biological maturation. An effective protocol for cryopreservation of seeds in liquid nitrogen has been developed, and the stimulating effect of ultralow temperature on seed germination has been shown. The duration of seed stratification for seedlings was determined.